Reinventing architecture through interpretation and reproduction - Kristanti Dewi Paramita (ARSNET, 2023)
Reinvention of architecture searches for new ways of interpreting and reproducing the materiality, the representation, and the critical discourse of architecture. Technological shifts, socio-cultural changes, the existence of new media become the primary driver of such reinvention. The collection of articles in this issue of ARSNET explores the different perspectives and urgencies of reinventing architecture. In doing so, the continuous quest of architectural reinvention enables a thorough and deep reading on the various dimensions and articulation of space.